Knowledge of Hypertensive Patients Affects Blood Pressure Reduction - Monika, Viki Indah; Vanchapo, Antonius Rino; Jayadi, Alpian; Lewar, Emanuel Suban Bala; Tusi, Juandri Seprianto; Mark, Elladdadi; Maharjan, Kailie (Journal of World Future Medicine, Health and Nursing, 2023)
Hypertension is a disease that is often referred to as the Silent Killer, high blood pressure which often does not cause symptoms, is referred to as hypertension when the blood pressure is more than 140/90 mmHg. Knowledge about how to lower blood pressure is very important for people with hypertension. However, several reviews and case reports presenting data on hypertension for lowering blood pressure provide different conclusions. Therefore, the authors are interested in systematically examining the factors that influence blood pressure increases. Articles were searched through the database from 2018 to 2022. Searches were obtained from PUBMED. The keywords used are "Hypertension and Health Knowledge, Attitudes, Practice and Cross Sectional". Search articles are filtered using Free full text and in English or Indonesian. Subjects were confirmed patients with hypertension over 18 years of age. The design in this study uses cross-sectional. Based on the results of the review, it was found that 6 articles met the inclusion criteria and estimated that hypertension sufferers in reducing blood pressure greatly influenced knowledge.